Implikatur Tegur Sapa dalam Bahasa Melayu Bengkulu - Jelita Zakaria; Ira Yuniati; Erwin Fajar Wijaya (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2021)
This study aims to describe the implicatures in Bengkulu Malay greetings in Teluk Segara District, Bengkulu City. The method used is descriptive method. Based on the results of the research on the greeting implicatures in the Bengkulu Malay language greeting in the Teluk Segara sub-district, Bengkulu City, it can be concluded that there are 22 greeting implicatures which are divided into two, namely, a) conversation implicature with 3 data; b) conventional implicature as many as 19 data. Keywords: Bengkulu Malay, Implicature, Greet Greetings